Hubungan Kebijakan Pemberdayaan Aparat Pemerintah Desa Dengan Percepatan Keberhasilan Pembangunan - Manabung, Shinta; Lengkong, Florence Daicy; Rompas, Sonny (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Since the implementation of the Act. Number 32 of 2004 on Regional Government, the localgovernment in Indonesia has entered a new era known as the era of regional autonomy. This bringsthe consequence that in order to optimize or accelerate the success of development in various regions,including rural development, required the support or participation of all components; and one ofthemain component that exist at the village level is the village officails. This study aimed to:"determine the relationship between the empowerment of village government policy to accelerate thesuccess of development in Sub Kendahe Sangihe Islands District". This research uses descriptivemethod with quantitative approach. The instrument used in this study to capture the primary data is aquestionnaire or a list of questions and assisted with interview guides (interviewguide).Results of thisstudy are expected to provide benefits, both theoretically and practically. Theoretically, the results ofthis study are expected to enrich the social sciences, particularly in the field of public administrationstudies. In practical terms, the results of this study are also expected to contribute ideas for policymakers, especially government district Sangihe Islands to improve the quality of personnelpemerintrah villages, especially in the villages in the subdistrict Kendahe Sangihe Islands Regencyforward through improved guidance systems and empowerment of the government apparatus village.Keywords : Relation,Policy.Building Success